2003
DOI: 10.1292/jvms.65.857
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Analysis of Peripheral Blood Mononuclear Cells Induced by Experimental Endotoxemia in Horse

Abstract: ABSTRACT. Cellular activation and functional cell surface markers were evaluated during experimentally-induced endotoxemia in healthy horses. Eight healthy adult horses were infused a low dose of endotoxin (lipopolysaccharide from Escherichia coli O26: B6, 30 ng/kg of body weight, IV) and five control horses were given an equivalent volume of sterile saline solution. Venous blood samples were collected for flow cytometric analysis of peripheral blood mononuclear cells (PBMCs) and to measure plasma endotoxin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…[13][14][15][16][17] In 1 study, 17 IV administration of E coli O55:B5 LPS at a dose of 30 ng/kg decreased the WBC count, compared with baseline values, and the nadir occurred 2 hours after infusion. [13][14][15][16][17] In 1 study, 17 IV administration of E coli O55:B5 LPS at a dose of 30 ng/kg decreased the WBC count, compared with baseline values, and the nadir occurred 2 hours after infusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] In 1 study, 17 IV administration of E coli O55:B5 LPS at a dose of 30 ng/kg decreased the WBC count, compared with baseline values, and the nadir occurred 2 hours after infusion. [13][14][15][16][17] In 1 study, 17 IV administration of E coli O55:B5 LPS at a dose of 30 ng/kg decreased the WBC count, compared with baseline values, and the nadir occurred 2 hours after infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of a high dose of LPS (125 µg/kg) to ponies induces hyperglycemia within the first hour, followed by significant hypoglycemia, compared with blood glucose concentrations before endotoxin administration; however, plasma insulin concentrations remained unchanged. [13][14][15][16][17] However, endotoxemia may still play a role in the development of laminitis, and this method allows physiologic responses to LPS administration to be isolated and studied. 12 If IR is an important risk factor for laminitis, then endotoxemia may exacerbate this disturbance in glucose metabolism and further increase the risk of disease.…”
mentioning
confidence: 99%
“…The administration of CD14-antibodies was effective in preventing septic shock even when administered after LPS exposure. In horses infused with endotoxin, the expression of CD14 on PBMCs increases and a correlation between this enhanced expression and the clinical signs of endotoxic shock was reported (Kiku et al 2003). CD14 is involved in the clearance of gram negative pathogens during infection and improves the sensitivity of the immune system to infection (Haziot et al 1994).…”
Section: Membrane-associated Moleculesmentioning
confidence: 99%
“…Moreover, CD14 mAbs that block LPS-CD14 binding protected against organ injury and death in an in vivo rabbit model of endotoxic shock (Schimke et al 1998). In horses infused with endotoxin, the expression of CD14 on peripheral blood mononuclear cells (PBMCs) increased and authors reported a correlation between this enhanced expression and the clinical signs of endotoxic shock (Kiku et al 2003). Additionally, different bacterial products utilise CD14 as a binding protein, which subsequently transports these products to their respective receptors on the cell membrane (Delude et al 1995;Muroi et al 2002).…”
Section: Cluster-of-differentiation Antigen 14mentioning
confidence: 99%